Monitoring of environmental studies during storage of drilling waste - Kustysheva I.N.; Kustysheva A.D. (BIO Web of Conferences)
Intensive exploitation of hydrocarbon resources and related processing products creates significant risks for vulnerable natural ecosystems, especially ecosystems of the Far North. This study is devoted to monitoring the environmental and radiation assessment of drilling waste, which is an important step towards their effective disposal. The article considers current problems arising during the disposal of drilling waste, as well as modern approaches to solving these issues. The main attention is paid to conducting a comprehensive assessment of the environmental and radiation state of drilling waste associated with the development of oil and gas fields. The purpose of this study is to formulate recommendations for the application of technological methods for processing drill cuttings for its subsequent use as an experimental building material for road surfaces.